Water Sanitation and Stunting Incident in Banggae District, Majene Regency, West Sulawesi - Ningsi, Nurpatwa Wilda; Mayangsari, Riska; Abdullah, Anisa Dwirizky (Sarana Ilmu Indonesia (salnesia), 2024)
SSGI 2022 showed that stunting’s prevalence rate in West Sulawesi is 35%, which is the second highest in Indonesia. Majene had the highest stunting prevalence rate in West Sulawesi in 2022, namely 40,6%. This study aimed to determine environmental factors (sanitation and exposure to cigarette smoke) that could affect children's development and could have an effect on increasing the incidence of stunting in toddlers. This research was carried out in Banggae District using case control study from April until June in 2023. The population in this study were 24 to 59-month-old toddlers. This research used a simple random study to obtain sample as many as 66 subjects. The instruments used in this study were a questionnaire sheet containing information about the characteristics of mothers and children, water intake descriptions, and environmental sanitation in the past two years. All obtained data were analyzed using univariate and bivariate chi-square tests to determine the relationship between all variables. The statistical test results for the relationship between drinking water sources and stunting were a p-value=0,012 (<0,05) and p-value=0,018 (<0,05) for the relationship between water processing and stunting. The chi-square test results for the relationship between the quality of physical water and stunting in children were a p-value=0,001 (<0,05) and an OR value of 0,320. The conclusion of this study is that several environmental factors, such as sanitation and exposure to secondhand smoke, can affect child development and significantly affect the number of stunting in children in Banggae, Majene, West Sulawesi.